The Role of Artificial Intelligence (AI) in Vocational Education - Atik Suparyati; Indah Widiastuti; Ida Nugroho Saputro; Nugroho Agung Pambudi (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan)
Artificial Intelligence is a technology that has rapidly developed in this decade. Its capability to perform tasks previously achievable only by humans has made this technology popular and utilized across various sectors, including vocational education. In vocational education, Artificial Intelligence plays a role in enhancing the efficiency and effectiveness of teaching. One example is the development of adaptive learning programs that can adjust the curriculum according to students' abilities and needs. Additionally, Artificial Intelligence is also used to evaluate student performance and provide automatic feedback. This system can assist in assessing and monitoring student performance, enabling teachers to focus on teaching and student development. This study used the Systematic Literature Review (SLR) method. This method is used to identify, assess, evaluate, and interpret all available research within the field of the relevant phenomenon, guided by specific research questions. By using this method, a systematic review and identification of journals can be conducted, following predefined steps. The data for this study is obtained from relevant journals between the years 2013 to 2021, totaling 15 literature journals from various countries. The primary goal of this research is to provide a deeper understanding of the role of this technology in vocational education and to present a framework that can be used as a guide for the implementation of Artificial Intelligence. It is anticipated that this research will assist educators and decision-makers in effectively utilizing Artificial Intelligence to enhance learning, skills, and vocational student preparation for the continually evolving job market.